2017
DOI: 10.1108/ijrdm-03-2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

Exploring channel conflict in an emerging economy: the small retailer’s perspective

Abstract: Purpose The purpose of this paper is to explore channel conflict from the small retailer’s perspective in the context of emerging economies. The study investigates the factors and probable outcomes of perceived channel conflict. Design/methodology/approach A qualitative research design is adopted. This study involves semi-structured in-depth interviews with 14 small retailers, selected through the purposive sampling technique, in a capital city of North India. Findings This exploratory study reveals five k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…In total, 13 per cent of the sampled firms were from Jordan (12 firms), 32 per cent from Saudi Arabia (29 firms are similar in the way they run their operations and the overall business environment (Belwal and Belwal, 2017). This applies also to most distribution channels in emerging markets (Satyam et al, 2017). Moreover, recent research (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 13 per cent of the sampled firms were from Jordan (12 firms), 32 per cent from Saudi Arabia (29 firms are similar in the way they run their operations and the overall business environment (Belwal and Belwal, 2017). This applies also to most distribution channels in emerging markets (Satyam et al, 2017). Moreover, recent research (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Distribution is the logistics function, which is responsible for the physical movement of goods and services downstream the supply chain towards retailers and end users (Eng, 2016;Rexhausen et al, 2012;Satyam et al, 2017). Warehousing and distribution functions have long been studied jointly due to their major role in the outbound logistics operations and delivering goods to retail stores (Hübner et al, 2016;Rexhausen et al, 2012; Von der Gracht and Darkow, 2010;).…”
Section: The Role Of Distribution Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shahidullah and Haque (2010) proposed a closer linkage between the producers and processors through vertical integration in the value chain for a reasonable price, quality, lead time and overall control of the supply chain. Lamont (1992) discussed the concept of the vertical and horizontal integration for the potato seed industries in The Netherlands and Northern Ireland whereas similar kinds of such studies are reported in the literature such as business relationship improvement (Hadjikhani and Thilenius, 2005;Gebauer et al, 2007), vertical integration (Nugent and Hamblin, 1996;Cook, 1997;Howe, 1998;Jennings, 2001;Leach et al, 2001;Charlebois and Camp, 2007;Gueimonde-Canto et al, 2011;Lamprinopoulou and Tregear, 2011;Dabas et al, 2012;Ding and Mahbubani, 2013), level of vertical integration selection (Priyadarshi and Routroy, 2018), comprising of subtopics such as strategic management (Parker et al, 2015), internationalization of retailing for rural entrepreneurs (Mudambi, 1994;Muñiz-Martínez, 1998;Johansson, 2002;Aygün and Oeser, 2017;Satyam et al, 2017), distribution (Brockman and Morgan, 1999), strategic ties (Orozco Quintero and Berkes, 2010;Dunham et al, 2012;Yi et al, 2012;Mehrotra and Verma, 2015), rural entrepreneurship (Saunders and Bromwich, 2012), economic performance (Peyrefitte et al, 2002), women entrepreneurship (Khera and Nayak, 2009;Yadav and Goyal, 2015;Bhardwaj, 2018) and improved information exchange among the supply chain members (Trim and Lee, 2006;Nandonde and K...…”
Section: Literature Reviewmentioning
confidence: 87%